The Use of National Minority Culture in Tourism Development - Pusztai, Bertalan (Ethnographica et Folkloristica Carpathica, 2024)
In our tourist travels, we seek experiences in locales distinct from our places of residence or work. Tourism developments strive to fulfil this desire by showcasing and making tangible some unique local characteristic, thus attracting visitors to a specific place. In resource-poor areas, one of the simplest and least investment-demanding ways to achieve this is by turning a unique element of local culture into an attraction and celebrating it. This does not require costly infrastructure development, but it can still attract tourists. Our study focuses on these local celebrations, which are most often referred to as festivals, feasts or competitions. In the first part of this paper, our goal is to draw attention to a specific group of local festivals, events that focus on the culture of national minorities. Along with examples from Hungary, we present in more detail two festivals: one in Southwest Hungary’s Feked and the other in Southeast Hungary’s Deszk. In the second part of the study, we categorise local festivals based on the cultural elements they highlight. According to my research, four basic categories can be determined. Festivals can be created to celebrate a well-identifiable local cultural or economic phenomenon. There are local celebrations aimed at preserving or reviving disappearing or vanished local cultural elements. There are festivals that emphasise newly invented traditions. Finally, events based on humour or randomness can also be the basis of a tourist attraction.